Inactivation of Escherichia coli O157:H7 using ultraviolet light-treated bacteriophages. (January 2016) - Hudson, JA; Billington, C; Premaratne, A; On, SLW
Escherichia coli O157:H7 causes serious foodborne infections warranting the development of effective control measures. One control option is to use bacteriophages (phages), which are regarded as safe to humans and an environmentally friendly alternative to chemical antimicrobials. One of the few remaining safety concerns is the potential for phages to facilitate genetic exchange between bacteria so resulting in undesirable mobilisation of genes. UV treatment of phages causes a rapid loss in their ability to replicate, while maintaining their antibacterial activity, and so the use of UV-treated phages could be an alternative to the use of viable phages. Data presented here show the inactivation of E. coli O157:H7 by UV-treated phages in milk and on the surface of raw and cooked meat. A minimum concentration of approximately 10 5 PFU cm −2 (pre-UV treatment titre) of UV-treated phages was required before inactivation of E. coli O157:H7 on the surface of meat was measurable, and 1–2 log10 CFU cm −2 reductions were typically obtained at concentrations of around 10 7 UV-treated phages cm −2 (pre-UV treatment titre). Inactivation of E. coli O157:H7 by UV-treated phages was less than that for untreated phages. The production of UV-treated phages was not optimised and it is possible that better reductions in pathogen concentration could be achieved for the same input UV-treated phages concentrations.